THE CONSEQUENCES OF A FORCED MIGRATION SHOCK FOR THE ECONOMY OF A COUNTRY AT WAR: THE CASE OF UKRAINE - Evelina Kamyshnykova (Izdevnieciba "Baltija Publishing", 2023)
The full-scale war in Ukraine, which started with the Russian invasion in February 2022, has led to an unprecedented forced migration crisis not seen in Europe since the Second World War. The current Ukrainian forced displacement, which has no analogues in terms of its scale, geographical coverage, quantitative indicators and timeframe, represents an exceptional case to study in terms of its impact on the economic environment of the country of origin. The purpose of this paper is to identify and analyse the short- and long-term effects of the forced migration shock on the economy of a combatant country in the context of a full-scale war in Ukraine. Methodology. To address the task of classifying the economic consequences of a forced migration shock from the perspective of the country of origin, the publication uses the matrix diagram method. The matrix developed is based on two key characteristics that indicate the durability of the impact (short-term or long-term) and the nature of the impact (explicit or implicit). The analysis of the short-term and long-term effects of forced migration on the Ukrainian economy is based on macroeconomic statistics (key macroeconomic indicators, labour market indicators, public finance indicators, external sector statistics) in the pre-war period, the war period since 2022, and forecasts for 2024-2025. Results. Unlike regular labour migration, forced migration has a predominantly negative impact on the economy of a country of origin, both in the short and long term. The explicit effect of forced migration on the economic system of the country of origin is to damage the labour market. The implicit effects include a decrease in remittances, a reduction in production facilities, an increase in the budget deficit and regional budget imbalances, an increase in the level of external and internal debt, increased dependence on international aid, a decrease in consumption, investment and GDP growth rates. Practical implications. The practical results provide a basis for further research into policy measures to address the negative aspects of increasing migration processes in Ukraine, particularly with a view to the country's future post-war reconstruction. Value/Originality. The matrix developed to assess the impact of the forced migration shock provides a deeper understanding of the multifaceted effects of this phenomenon on the socio-economic system of a country at war.